Rapid incision of the Mekong River in the middle Miocene linked to monsoonal precipitation. Issue 12 (December 2018) - Nie, Junsheng; Ruetenik, Gregory; Gallagher, Kerry; Hoke, Gregory; Garzione, Carmala; Wang, Weitao; Stockli, Daniel; Hu, Xiaofei; Wang, Zhao; Wang, Ying; Stevens, Thomas; Danišík, Martin; et al.
Abstract The uplift of orogenic plateaus has been assumed to be coincident with the fluvial incision of the gorges that commonly cut plateau margins. The Mekong River, which drains the eastern Qiangtang Terrane and southeastern Tibetan Plateau, is one of the ten largest rivers in the world by water and sediment discharge. When the Mekong River was established remains highly debated—with estimates that range from more than 55 to less than 5 million years ago—despite being a key constraint on the elevation history of the Tibetan Plateau. Here we report low-temperature thermochronology data from river bedrock samples that reveal a phase of rapid downward incision (>700 m) of the Mekong River during the middle Miocene about 17 million years ago, long after the uplift of the central and southeastern Tibetan Plateau. However, this coincides with a period of enhanced East Asian summer monsoon precipitation over the region compared with the early Miocene. Using stream profile modelling, we demonstrate that such an increase in precipitation could have produced the observed incision in the Mekong River. In the absence of an obvious tectonic contribution, we suggest that the rapid incision of the Tibetan Plateau and the establishment of the Mekong River in the middle Miocene may be attributed to increased erosion during a period of high monsoon precipitation. Incision of the Mekong River that occurred after the uplift of the Tibetan Plateau may have been driven by a period of high monsoon precipitation, as suggested by age data from river bedrock samples and stream profile modelling.